Kepemimpinan yang Melayani Menurut Teladan Kristus [Servant Leadership According to Christ's Example] - Neneng Andriani (Universitas Pelita Harapan, 2024)
Every human being experiences leadership in their daily lives, as leadership is a process of influencing others. When someone tries to influence the thoughts, behaviours, or development of others in their personal or professional life, he is taking on the role as a leader. It is very important for a leader to understand how he will use his authority to influence others. The Christian has a very clear reference point in this matter, as the Bible is a foundation to determine how someone will lead, to lead like Jesus. The purpose of this paper is to describe the Christ-like leadership, which is servant leadership. Based on narrative stories about His life in the Bible, servant leadership was taught and practiced by Jesus Christ more than two thousand years ago, which is measured by His total commitment by serving fellow human beings. For Christian leaders, leadership as an act of service is not an option, but a command. Jesus served, so that we learn to serve with heart, head, hands, and habits. Servant leadership must be a living statement for those who live in Christ, which will be seen from the way they treat one another, and the way they introduce the love of Christ to the whole world.BAHASA INDONESIA ABSTRACT: Setiap manusia mengalami kepemimpinan dalam kehidupan sehari-hari, karena kepemimpinan adalah proses mempengaruhi orang lain. Ketika seseorang mencoba mempengaruhi pikiran, perilaku, atau perkembangan orang lain dalam kehidupan pribadi atau profesionalnya, dia mengambil peran sebagai pemimpin. Sangatlah penting bagi seorang pemimpin untuk memahami bagaimana ia akan menggunakan otoritasnya untuk mempengaruhi orang lain. Orang Kristen memiliki acuan yang sangat jelas dalam hal ini, karena Alkitab adalah dasar untuk menentukan bagaimana seseorang akan memimpin, memimpin seperti Yesus. Tujuan dari tulisan ini adalah untuk menggambarkan kepemimpinan seperti Kristus, yaitu kepemimpinan yang melayani. Berdasarkan kisah-kisah naratif tentang kehidupan-Nya di dalam Alkitab, kepemimpinan-pelayan telah diajarkan dan dipraktekkan oleh Yesus Kristus lebih dari dua ribu tahun yang lalu, yang dilihat dari komitmen-Nya yang total dalam melayani sesama manusia. Bagi para pemimpin Kristen, kepemimpinan sebagai tindakan melayani bukanlah sebuah pilihan, melainkan sebuah perintah. Yesus telah melayani, sehingga kita belajar untuk melayani dengan hati, kepala, tangan, dan kebiasaan. Kepemimpinan yang melayani harus menjadi pernyataan yang hidup bagi mereka yang hidup di dalam Kristus, yang akan terlihat dari cara mereka memperlakukan satu sama lain, dan cara mereka memperkenalkan kasih Kristus kepada seluruh dunia.